Implementation ‘Kembang Desa’ (Partnership of Village Building) as a BKP-MBKM Learning Model for Village Development - Kholifah, Emy Kholifah; Rahayu, Yeni Dwi; Wardhana, Danu Indra (POLITICO, 2023)
This study aims describe the implementation of 'Kembang Desa' as a tourism village development model. The need to accelerate the development of tourist villages, the need for a synergy of roles between various competent parties, and the need for a rationalization of the role of universities (students and lecturers) as agents of change in the community through the BKP-MBKM model for Village Development.Uuses a qualitative descriptive research method. The results of the study are the village development needs to be accelerated by increasing the use of natural potential, community potential, social institutional potential and local economic potential and local culture, as well as the potential of government officials to support the development of tourist villages. Kemiri Tourism Village which has the characteristics of a mountainside village, the direction of its development has the potential for natural beauty, the potential for agriculture-plantation and processing of agricultural products, and the unique culture of the community and various other local wisdoms of the community can be social capital for the development of tourist villages. This great potential needs to be developed through the alignment of innovative government policies by developing cooperation with various parties, including universities. Partnerships with Universities can be realized through the implementation of the Village Development BKP MBKM. ‘Kembang Desa’ Model has succeeded in realizing university advocacy on the development of Kemiri Tourism Village